Hey guys, I'm having trouble understanding an aspect of u-substitution. In this problem:

Integrate: $\displaystyle x^3/(5*x^4+2)^3 * dx$

u = $\displaystyle 5*x^4 + 2$

$\displaystyle 1/20 * du = x^3 *dx$

So that takes care of the $\displaystyle x^3 * dx$ in the first equation, and the rest of the integration is easy.

But I don't understand why the same principle can't be applied here:

Integrate: $\displaystyle x * sqrt(x-3) * dx $

u = x-3

du = x * dx

Why can't you cancel out x * dx with du here?

Thanks in advance for any help.